2021
DOI: 10.24191/ajue.v17i3.14497
|View full text |Cite
|
Sign up to set email alerts
|

Students' Satisfaction towards Academic Advising Service

Abstract: Effective academic advising service has been found to bring positive benefits to educational institutions to increase students' retention rates and graduation. This study sought to find the essential attributes in public university academic advising service in UiTM Pasir Gudang campus, Malaysia, which may be used to improve the service provided to the students. Quantitative research was conducted using a questionnaire adapted from Parasuraman's SERVQUAL model with a sample size of 221. The study aimed to exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Because of its significant impact on the education system, academic advising in higher education is considered to affect learners’ academic performance, enhance their learning experience and employment, and help them achieve success [ 9 , 10 ]. It can also increase student retention rates, graduation rate satisfaction and loyalty [ 11 ], and eventually lead to an effective measure of the win-win situation of achieving educational goals and fulfilling the educational mission of the school [ 12 ]. Therefore, it is particularly important to propose a good academic counseling program.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its significant impact on the education system, academic advising in higher education is considered to affect learners’ academic performance, enhance their learning experience and employment, and help them achieve success [ 9 , 10 ]. It can also increase student retention rates, graduation rate satisfaction and loyalty [ 11 ], and eventually lead to an effective measure of the win-win situation of achieving educational goals and fulfilling the educational mission of the school [ 12 ]. Therefore, it is particularly important to propose a good academic counseling program.…”
Section: Introductionmentioning
confidence: 99%
“…"While academic advising services may differ between undergraduate and postgraduate education (Güven, 2014), the general content of these services can be described as providing information (Bektaş Köser, 2010) on department and faculty, relationships with other staff members within the faculty, course content, regulations, available services, scholarship opportunities, health and social services, as well as tasks such as course registration and program planning, monitoring the student's status (attendance, academic performance), assisting in future planning, and supporting the exploration of the student's abilities (Crookston, 1994;Demir, 1995;Tuttle, 2000;Çeçener, Güneş, and Akansel, 2021;Ismail, Roslan, Ismail, and Salleh, 2021). In addition to guiding students, academics also engage in various academic and administrative tasks such as peer reviewing in academic studies, conducting research, and serving on university committees (Kuzgun et al, 1997;Aypay, 2006;White and Schulenberg, 2012;White, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The research of Donaldson et al (2016) has shown that guardian lecturers help to shape students' culture using information and features to formulate academic plans, demonstrate decision-making, familiarize undergraduates with campus policies and procedures, as well as allow them to achieve their future careers. Effective academic advisory services have been found to bring positive benefits to educational institutions to increase student retention and graduation rates (Ismail et al, 2021). Academic advising must be emancipatory to be critical (Winham, 2020).…”
Section: Introductionmentioning
confidence: 99%